Realisation of e-government initiatives in Singapore. - Loh, Soo Yen. (2008)
E-government is the latest government reform movement worldwide. It harnesses the power of information technology to enable government to deliver better services and to govern better. This thesis seeks to provide an overview of e-government trends worldwide and to analyse the progress of Singapore in the e-government journey.